2004
DOI: 10.1080/00779950409544392
|View full text |Cite
|
Sign up to set email alerts
|

Wage and employment rates in New Zealand from 1991 to 2001

Abstract: This paper examines the simultaneous determinants of employment and wage rates for people of working age in New Zealand. The determinants are as anticipated and similar to results in other countries. In addition to the effects of the usual variables (such as, education, age, family composition), it is found that unemployment affects the probability of employment negatively, but has no effect on wage rates, living with one's parents decreases the employment probability of singles but increases it for sole paren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
24
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 7 publications
3
24
2
Order By: Relevance
“…Since the first version was completed in 2000, and described in detail in , it has undergone a range of substantial developments. In the present version of MITTS, SIHC data from 1994/1995, 1995/1996, 1996/1997, 1997/1998, 1999/2000, 2000/2001, 2002/2004 can be used. One set of econometric estimates of preferences underlying the behavioural responses are based on data observed between 1994 and 1998 and another set is based on data observed between 1999 and 2004.…”
Section: Mittsmentioning
confidence: 99%
“…Since the first version was completed in 2000, and described in detail in , it has undergone a range of substantial developments. In the present version of MITTS, SIHC data from 1994/1995, 1995/1996, 1996/1997, 1997/1998, 1999/2000, 2000/2001, 2002/2004 can be used. One set of econometric estimates of preferences underlying the behavioural responses are based on data observed between 1994 and 1998 and another set is based on data observed between 1999 and 2004.…”
Section: Mittsmentioning
confidence: 99%
“…Duncan, Giles and MacCrae (1999) found strong effects for sole parents (mostly women) and married women in the United Kingdom of both the age of the youngest child and the number of preschool children. In New Zealand, Kalb and Scutella (2004) found strong effects of the age of the youngest child on the labour supply for sole parents (mostly women) and partnered women. Preschool‐aged children affect the labour supply to a larger extent than do children aged greater than 5 years old.…”
Section: Presence Of Children and Labour Supplymentioning
confidence: 99%
“…Fraker and Moffitt (1988), Hagstrom (1996), Hoynes (1996), Aaberge, Colombino and Strøm (1999) and Van Soest, Das and Gong (2002) found effects for married women in the United States and Europe. In New Zealand, Kalb and Scutella (2004) found strong effects of the number of children on the labour supply for sole parents (who are mostly women) and partnered women.…”
Section: Presence Of Children and Labour Supplymentioning
confidence: 99%
“…The model was based on the Melbourne Institute Tax and Transfer Simulator (MITTS); see Creedy et al (). The main work involved in producing TaxMod‐B, including estimation of wage functions and preference functions for various demographic groups, was carried out by Kalb and Scutella (, ).…”
mentioning
confidence: 99%
“…Indeed, Kalb and Scutella () and Mercante and Mok () found that the estimated preference functions for sole parents and single adults without children displayed substantial differences.…”
mentioning
confidence: 99%